Grabbybitez / Nurnazurah Anaqi Mohd Arif … [et al.] - Mohd Arif, Nurnazurah Anaqi; Halmi, Nur Fatihah; Mohd Puad, Nurul Syuhada; Mohd Shamsol Amri, Siti Syahmimi; Johari, Muhammad Aiman Zulkhairy; Harin, Norazman (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
I witness the challenges that my disabled customers face when it comes to ordering food. One of them with wheelchair once told me, expressing their problem with table because our tables are not easily accessible for them. The low height of our tables makes it hard for these individuals to comfortably reach their food and eat at a comfortable distance from the table. Grabbybitez provides a special portable table for people with disabilities. This table has multiple functions. This table has a rail that provides food to make it easier for disabled customers. Apart from that, this table also has various buttons that work to facilitate special customers. Here are the buttons on the table and their functions, the button to call the server, the button to adjust the table, the button to adjust the chair, the voice sensor button for new customers, and the button to prepare the spoon and fork. Touch Table: Interactive, braille equipped touchscreen tables, Click Serve: Table buttons for service, with braille support, Cutlery Click: Instant utensil dispensing via button press, braille-enabled, Seat Click: Chair summoning with a button, braille-integrated, Adjustable Tables: Customizable height and position, with braille, Censored Click: Smart sensing for attentive service, braille-inclusive, Conveyor Sound: Automated dish notification system, with braille. GrabbyBitez's innovative table provides convenience with a conveyor belt system and customizable settings, enhancing dining independence for disabled customers without having to rely on anyone. Enjoy easy server access, adjustable tables, and automated utensil preparation for an inclusive dining experience.